International journal of Digital Earth - International Society for Digital Earth (Taylor & Francis, 2008)
"'International Journal of Digital Earth' is a journal focusing on the theories, technologies, applications and societal implications of Digital Earth. It is the official journal of the International Society for Digital Earth. The journal is a response to the Digital Earth initiative and its aim to improve social conditions, protect the environment, and support future sustainable development. 'International Journal of Digital Earth' welcomes papers that : progress visions for Digital Earth frameworks, policies, and standard ; explore geographically referenced 3D, 4D, or 5D models to represent the real planet, and geo-data-intensive science and discovery ; develop methods that turn all forms of geo-referenced data, from scientific to social, into useful information that can be analyzed, visualized, and shared ; present innovative, operational applications and pilots of Digital Earth technologies at a local, national, regional, and global level ; expand the role of Digital Earth in the fields of Earth science, including climate change, adaptation and health related issues, natural disasters, new energy sources, agricultural and food security, and urban planning ; foster the use of web-based public-domain platforms, social networks, and location-based services for the sharing of digital data, models, and information about the virtual Earth ; explore the role of social media and citizen-provided data in generating geo-referenced information in the spatial sciences and technologies."--taken from Taylor and Francis Online web site viewed May 18, 2023.
Keywords: Global environmental change : Research : Periodicals; Global environmental change : Remote sensing : Periodicals; Geographic information systems : Periodicals; Changement global (Environnement) : Recherche : Périodiques; Changement global (Environnement) : Télédétection : Périodiques; Geographic information systems; Global environmental change : Research